Vision of Sri Aurobindo’s Nation Building and Educational Transformation - Bhawani Singh Rajawat; Chitra Dashora (International Journal of Education Sciences, 2025)
The primary goal of the current study is to examine Shri Aurobindo's contributions to educational reform and nation-building, with an emphasis on how applicable they are to the current educational framework. The renowned philosopher and educationist Shri Aurobindo put out theories about education that are still astonishingly successful today. English literature and educational concepts serve as the main foundation for this course, which has a nationalism-based orientation. To gather and examine data, the study consults both primary and secondary sources (approved literature). In order to cultivate the potential of the human mind and spirit, Shri Aurobindo highlighted the importance of dynamic and creative education. His approach to education fosters moral, intellectual, physical, and spiritual development by integrating holistic development. Furthermore, his idea of nationalism promoted a spiritual component to national identity and advancement, drawing inspiration from Vedanta philosophy and spiritual development. This study emphasizes how important Shri Aurobindo's theories are for solving today's educational problems. His idea of combining education with intellectual and spiritual development provides a revolutionary perspective to contemporary education. The study also emphasizes how crucial it is to combine traditional values with cutting-edge teaching strategies in order to develop an educational system that develops students' character and conscience in addition to providing them with knowledge. This study offers ways to improve and modify the current educational system for all-around development by examining Shri Aurobindo's educational and national aspirations.
Keywords: Shri Aurobindo’s nationalism; educational ideas; philosophy; social problems; social utility; spiritual development; women education